Effect of age and systemic inflammation on the association between severity of periodontitis and blood pressure in periodontitis patients - Hongjia Yang; Yixuan Qin; Jiaqi Geng; Jinyue Qu; Qian Cheng; Kuibao Li; Dongxue Zhang (BMC Oral Health, 2025)
Abstract Background Periodontitis is a periodontal inflammatory disease closely related to hypertension. However, the role of age and systemic inflammation is unclear. This study examined the effect of age and systemic inflammation on the association between severity of periodontitis and blood pressure in periodontitis patients. Methods This cross-sectional clinical study included periodontitis patients treated at Beijing Chaoyang Hospital, Capital Medical University from January 2020 to July 2023. Patients with periodontitis were included using inclusion and exclusion criteria, and data on basic information, blood pressure, periodontal examination indicators, and biochemical examination indicators were collected. Patients were grouped by blood pressure, and differences in basic information, blood indexes, and periodontal examination indexes between the two groups were compared by independent sample T-test. With PBOP as independent variables, systolic blood pressure (SBP) and diastolic blood pressure as dependent variables, and several indexes as covariables, the relationship between them was studied by linear regression. The interaction was used to explore the relationship between age and systemic inflammation in periodontitis and hypertension. Results A total of 144 patients with periodontitis were enrolled. In fully adjusted analyses, the percentage of site with bleeding on probing (PBOP) was significantly associated with SBP (B = 10.08, p = 0.027) in the overall group. In patients 50 years or older, but not in those younger than 50, PBOP remained significantly associated with SBP (p = 0.018 for interaction). The strength of association between PBOP and SBP was greater in patients with higher systemic immune-inflammation index. The regression coefficients of PBOP in the systemic immune-inflammation index ≥ 400 and < 400 groups were 16.61 (95% CI, 3.32–29.90; p = 0.015) and 13.69 (95% CI, 1.15–26.23; p = 0.033), respectively (p = 0.047 for interaction). Similar results were observed in the systemic inflammation response index ≥ 9 and < 9 groups (B = 17.04 (95% CI, 2.66–31.42, p = 0.021) and 13.98 (95% CI, 1.94–26.01, p = 0.024 respectively; p = 0.028 for interaction). Conclusions This study indicates a significant association between the severity of periodontitis and SBP, which was modified by age and systemic inflammation.